2011
DOI: 10.1007/s11906-011-0231-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Relaxin on Arterial Dilation, Remodeling, and Mechanical Properties

Abstract: Administering relaxin to conscious rats and humans elicits systemic and renal vasodilation. The molecular mechanisms vary according to the duration of relaxin exposure-so-called "rapid" (within minutes) or "sustained" (hours to days) vasodilatory responses-both being endothelium-dependent. Rapid responses are mediated by G(αi/o) protein coupling to phosphoinositol-3 kinase/Akt (protein kinase B)-dependent phosphorylation and activation of nitric oxide synthase. Sustained responses are mediated by vascular endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 82 publications
(103 reference statements)
1
68
0
2
Order By: Relevance
“…In regards to the cardiovascular system, in both male and female humans and rats, chronic administration of RLX causes vascular remodeling, angiogenesis, and systemic vasodilation (8). Endogenous RLX is a major contributor to peripheral vasodilation and augmented renal function seen in pregnancy, and recent clinical trials suggest that exogenously administered RLX may have therapeutic value in treating heart-failure patients (2,8,14).In addition to peripheral vascular effects, circulating RLX plays an important role in the central nervous system (CNS) regulation of fluid and electrolyte balance during pregnancy via activation of projection neurons originating in forebrain circumventricular organs. In the first half of pregnancy, RLX, through an ANG II-dependent mechanism in the subfornical organ (SFO), plays a critical role in central resetting of arginine-vasopressin (AVP) secretion, contributing to the expanded plasma volume in pregnancy (18,28,34,39).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In regards to the cardiovascular system, in both male and female humans and rats, chronic administration of RLX causes vascular remodeling, angiogenesis, and systemic vasodilation (8). Endogenous RLX is a major contributor to peripheral vasodilation and augmented renal function seen in pregnancy, and recent clinical trials suggest that exogenously administered RLX may have therapeutic value in treating heart-failure patients (2,8,14).In addition to peripheral vascular effects, circulating RLX plays an important role in the central nervous system (CNS) regulation of fluid and electrolyte balance during pregnancy via activation of projection neurons originating in forebrain circumventricular organs. In the first half of pregnancy, RLX, through an ANG II-dependent mechanism in the subfornical organ (SFO), plays a critical role in central resetting of arginine-vasopressin (AVP) secretion, contributing to the expanded plasma volume in pregnancy (18,28,34,39).…”
mentioning
confidence: 99%
“…In regards to the cardiovascular system, in both male and female humans and rats, chronic administration of RLX causes vascular remodeling, angiogenesis, and systemic vasodilation (8). Endogenous RLX is a major contributor to peripheral vasodilation and augmented renal function seen in pregnancy, and recent clinical trials suggest that exogenously administered RLX may have therapeutic value in treating heart-failure patients (2,8,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The in-hospital and 30-day mortality rates modeling and passive mechanical properties. 12,17, 18 The ability of serelaxin to benefit patients with AHF by inducing similar changes was recently evaluated in phase-II and phase-III clinical trials. 9,11,19 A safety and tolerability phase-I trial assessed the effects of sequential dose levels of serelaxin in 16 patients with chronic HF, 7,11 and demonstrated that serelaxin (10-960μg · kg -1 · day -1 IV for 24 h) was well-tolerated, produced hemodynamic effects consistent with vasodilation and improved markers of renal function without adverse consequences.…”
Section: Pathophysiology and Classifications Of Ahfmentioning
confidence: 99%
“…Relaxin was shown to promote vasodilation, cardioprotection, antifibrotic wound healing, and angiogenesis (Brecht et al ., 2011; Conrad and Shroff, 2011; Du et al ., 2010). In various tumors, the RLN2‐RXFP1 has emerged as an important ligand–receptor system involved in controlling growth, migration/tissue invasion, angiogenesis, and metastasis (Klonisch et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%